Interdisciplinary Implementations of Some Chemical Statistical Schemes - AKKARTAL, ERKUT (Asian Journal of Chemistry, 2010)
The aim of the present investigation is to study an interdisciplinary application on chemical, biometrical and econometrical models. Regression analysis and least square methods used in some statistical processes and/or econometrical studies are sometimes similar with the methods used in biochemistry and ship design. Especially, as far as a biometrical data set including structural change and designing the board side of the ship is concerned, some smoothing techniques are used, like the ones in used econometrics. In this study the common ways of statistical scheme and ship designing and biochemistry models are evaluated and some similar processes are emphasized.